On the non-loсal theory of the high-temperature superconductivity - B. V. Alexeev (Тонкие химические технологии)
The possibility of the non-local physics application in the theory of superconductivity was investigated. It is shown that under the superconducting conditions the relay motion of the soliton system («lattice ion - electron») is realized when chemical bonds are absent. In terms of quantum hydrodynamics the problem of creation of high temperature superconductors is reduced to finding materials, the lattices of which could realize the soliton motion without destruction. These materials should be created using the technology of quantum dots.